Lactate levels during anesthesia in patients undergoing craniopharyngioma surgery - Shen, Xiaoxu; Cao, Xiaoyun; Che, Xuehua; Wang, Kaiyu; Qiao, Nidan (Frontiers in Surgery, 2025)
PurposeTo assess the incidence of hyperlactatemia and lactic acidosis in patients undergoing craniopharyngioma surgery and to investigate their association with surgical outcomes.MethodWe analyzed clinical data from all patients who underwent craniopharyngioma surgery between 2019 and 2023 at a tertiary care center. Arterial blood gas analyses were performed prior to anesthesia and at one-hour intervals during surgery. Patients were classified into three groups: the Lactic Acidosis group (LA), Hyperlactatemia group (HL), and Normal Control group (NC). The primary outcome was the occurrence of postoperative severe hypernatremia (serum sodium levels exceeding 155 mmol/L).ResultsWe enrolled 261 patients with a mean age of 41.7 years. During anesthesia, mean lactate levels increased from 1.4 [1.0–1.9] mmol/L at initiation to 4.6 [1.8–7.0] mmol/L after 8 h. Among the cohort, 44 patients (16.9%) were classified in the HL group and 31 patients (11.9%) in the LA group. Anesthesia duration was the sole factor significantly associated with increased lactate levels in both univariate and multivariable analyses (OR 1.50 [95% CI: 1.31–1.80], p < 0.001). The elevated lactate level was independently associated with hypernatremia, even after adjusting for potential confounders, with an odds ratio of 2.12 (95% CI: 1.04–4.24, p = 0.038). No significant differences were observed among the three groups regarding total hospital stay, ICU stay, or incidence of severe complications.ConclusionLactate levels increased during anesthesia in patients undergoing craniopharyngioma surgery and were associated with postoperative hypernatremia. However, with appropriate management, lactic acidosis was not significantly linked to adverse postoperative outcomes.